A verification approach for crosscutting features based on extension join points - Coelho, Roberta (2006)
Recently, one arguing question in the context of product line development is how to improve the modularization and composition of crosscutting features. However, little attention has been paid to the closely related issue of testing the crosscutting features. This paper proposes a verification approach for the crosscutting features of a product line based on the use of a previously proposed concept called Extension Join Points.